2022
DOI: 10.1186/s12876-022-02234-9
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the characteristics of long-term survivors among patients with gallbladder cancer with liver metastasis who underwent surgical treatment: a retrospective multicenter study (ACRoS1406)

Abstract: Background Gallbladder cancer (GBC) with liver metastasis is considered unresectable. However, there have been infrequent reports of long-term survival in patients with GBC and liver metastases. Therefore, we examined the characteristics of long-term survivors of gallbladder cancer with liver metastasis. Methods A retrospective multicenter study of 462 patients with GBC (mean age, 71 years; female, 51%) was performed. Although patients with pre-ope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…First, published studies supported debulking surgery to improve the outcome of metastatic GBC in the real world. Less liver metastasis was associated with improved OS in resected stage--IV GBC [12]. Either primary tumor resection or synchronous resection of the primary tumor and liver metastases can signi cantly prolong OS for metastatic GBC [11,13].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…First, published studies supported debulking surgery to improve the outcome of metastatic GBC in the real world. Less liver metastasis was associated with improved OS in resected stage--IV GBC [12]. Either primary tumor resection or synchronous resection of the primary tumor and liver metastases can signi cantly prolong OS for metastatic GBC [11,13].…”
Section: Discussionmentioning
confidence: 93%
“…Radical surgery is the only curative therapy for BTC and is generally applied for early stage disease; however, many retrospective studies have suggested that resection of tumors can prolong the survival outcome of advanced GBC, even in those with liver metastasis [11][12][13][14]. Hence, surgery following conversion therapy might be feasible for GBC with liver metastasis to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We further classified advanced GBC into four subtypes, which combined the information derived from radiological imaging findings and the feasibility of achieving en bloc resection. Therefore, limited resectable liver metastasis, which is traditionally classified as M1 in the TNM staging system but has benefited from surgery ( 20 ), is classified at the locally advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] GBC exhibits a highly aggressive behavior, and up to 70% of patients develop lymph node metastasis, liver metastasis, vascular invasion, perineural metastasis, or even distant metastasis, which limits the clinical therapeutic options owing to unresectable surgery and chemotherapy resistance. [ 2 ] Metastasis is the leading cause of cancer‐related deaths. Therefore, identifying the key drivers of the high metastatic potential of GBC is necessary.…”
Section: Introductionmentioning
confidence: 99%